2009
DOI: 10.1002/psc.1141
|View full text |Cite
|
Sign up to set email alerts
|

Side chain‐to‐side chain cyclization by click reaction

Abstract: Cu(I)-catalyzed azide-alkyne 1,3-dipolar Huisgen's cycloaddition (CuAAC) is a click reaction that has drawn a lot of attention, in general, and in the field of peptide and protein sciences, in particular. Among several reported applications, the preparation of novel heterodetic cyclopeptides by an intramolecular side chain-to-side chain CuAAC, forming a 1,4-disubstituted[1,2,3]triazolyl-containing bridge, is of great interest. Herein, we provide a detailed protocol for the syntheses of model heterodetic cyclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…This may explain the dramatic loss of potency of cyclopeptide 2 in comparison to the linear peptide reference. Our results confirm the negative effect of the substitution of Gln 6 and Gln 10 with a lactam bridge between Lys 6 and Glu 10 , as previously observed for an analogue of PTH- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). 30 In contrast to the classical lactam formation based on the Lys and Glu/Asp side chains, the cross-linking of two Ser side chains by a dicarboxylic acid offers the possibility to form a bridge of variable length and containing two ester bonds as potential hydrogen bond acceptors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may explain the dramatic loss of potency of cyclopeptide 2 in comparison to the linear peptide reference. Our results confirm the negative effect of the substitution of Gln 6 and Gln 10 with a lactam bridge between Lys 6 and Glu 10 , as previously observed for an analogue of PTH- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). 30 In contrast to the classical lactam formation based on the Lys and Glu/Asp side chains, the cross-linking of two Ser side chains by a dicarboxylic acid offers the possibility to form a bridge of variable length and containing two ester bonds as potential hydrogen bond acceptors.…”
Section: Discussionsupporting
confidence: 92%
“…SAR studies aiming at the minimization of the PTH length showed that substitutions of the native PTH residue Gln 6 are generally not tolerated, whereas the replacement of the native residue Asn 10 with Gln leads to an analogue with superior potency. 25 Gardella and co-workers 30 investigated the effect of a covalent linkage between the side chains at positions 6 and 10 on the potency of H-[Ala 3,12 ,Gln 10 ,Har 11 ,Trp 14 ]-rPTH- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) that was appropriately modified by the substitutions Lys 6 /Gln and Glu 10 /Gln and successively subjected to lactamization. Both the linear and the cyclic forms of the double-substituted analogue are much less potent than the starting analogue (130 and 21 μM, respectively, vs 0.12 μM).…”
Section: Resultsmentioning
confidence: 99%
“…The cyclization reaction is carried out on a newly developed polymeric support [64], both with and without side chain-protecting groups, and gives only the cyclomonomeric product. Two more recent examples of side chain-side chain peptide cyclization via azide-alkyne 1,3-dipolar cycloaddition have been reported [65,66]. In the first case, the attempted on-resin reaction between a lysine-derived w-azide and Pra failed to give the target cyclomonomer and only side reactions (including cyclodimerization) were observed, despite the wide range of conditions attempted [65].…”
Section: Click Chemistrymentioning
confidence: 94%
“…In the last 5 years, several examples have shown that the Cu(I)-mediated click reaction can be used as a cyclization aid for small peptides [64][65][66][67][68][69][70][71][72][73][74]. Meldal and co-workers have performed an intramolecular 1,3-dipolar cycloaddition between the side chains of propargylglycine (Pra) and 3-azidoalanine.…”
Section: Click Chemistrymentioning
confidence: 98%
See 1 more Smart Citation